Hyperelastic stretchable fluorescent shape memory dual-mode anti-fake information encryption electrospun fibrous membrane
Eu(TTA)3(TPPO)2/PCL/TPU electrospinning fiber membrane prepared through electrospinning technology solves the problem of high brittleness of existing fiber membrane materials, realizes the function of flexible, super elastic and stretchable, and has the ability to be equipped with Excellent red fluorescence and shape memory characteristics, suitable for high-level anti-counterfeiting and information encryption storage.
Patent Information
- Application Number
- CN202411434569.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
The existing polymer-based inorganic-organic composite electrospun fiber membrane materials are highly brittle, have limited service life and application scenarios, and are difficult to meet the functional needs of flexible, superelastic, stretchable.
Using electrospinning technology, PCL and TPU are used as the main polymers, combined with Eu(TTA)3(TPPO)2 ligand, Eu(TTA)3(TPPO)2/PCL/TPU electrospinned fiber membranes are prepared, with excellent red fluorescence and shape memory properties.
It realizes dual-mode anti-counterfeiting and information encryption storage, improves the anti-counterfeiting and information encryption level, and has super elastic tensile performance and good water resistance.
Smart Images

Figure CN119465519A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber material preparation, and in particular to a superelastic stretchable fluorescent shape memory dual-mode anti-counterfeiting information encrypted electrospun fiber membrane and a preparation technology thereof. Background Art
[0002] With the development of science and technology and the progress of society, counterfeit products are gradually increasing; important information leakage incidents also occur from time to time. Therefore, the development of advanced anti-counterfeiting and information encryption storage materials has become one of the frontier research areas of materials science.
[0003] Common polymer-based inorganic-organic composite electrospun fiber membrane materials, such as polystyrene PS, polymethyl methacrylate PMMA, polyvinyl pyrrolidone PVP-based composite fiber membranes, are very brittle, which greatly reduces their service life and application scenarios. Therefore, the development of flexible, super-elastic and stretchable functionalized electrospun fiber membrane materials is of great significance and has broad application prospects.
[0004] Thermoplastic polyurethane, referred to as TPU, usually has a melting point range of 130-136 ° C. Thermoplastic polyurethane TPU has been widely studied and applied due to its low cost, structural diversity, good elasticity, stretchability and easy modification.
[0005] Polycaprolactone, abbreviated as PCL, has a melting point range of 59-64 °C. PCL has good biocompatibility, is very soft, and has great stretchability; PCL also has good shape memory temperature control properties and is widely used in the production and processing of drug carriers, plasticizers, degradable plastics, shape memory materials, and nanofibers.
[0006] Rare earth metal europium complex Eu(TTA)3(TPPO)2,Eu 3+ It is europium ion, TTA is 2-thenoyltrifluoroacetone, and TPPO is triphenylphosphine oxide. Due to the unique electronic configuration of europium ion, it becomes a luminescent material with unique properties, such as high luminous intensity, good stability, high fluorescence quantum yield, good monochromaticity, etc. It is a widely used red fluorescent material.
[0007] U.S. Patent No. 1975504 discloses a technical solution for electrospinning, which is an effective method for preparing continuous micro-nano fibers with macroscopic length. It was first proposed by Formhals in 1934. This method is mainly used to prepare polymer nanofibers. Its characteristic is that the charged polymer solution or melt is pulled by the electrostatic force in the electrostatic field and ejected from the nozzle to the receiving screen on the opposite side, thereby achieving wire drawing. Then, the solvent evaporates at room temperature, or the melt is cooled to room temperature and solidified to obtain micro-nano fibers. For example, QZ Yu, et al. prepared polyaniline PANI nanofibers using electrospinning technology [ Mater. Sci. Eng. B , 2008, 150, 70-76]; Dong Xiangting et al. used a single spinneret and electrospinning technology to prepare PAN / Eu(BA)3phen composite luminescent nanofibers [New Chemical Materials, 2008, 36(9), 49-52]; Wang Ce et al. used a single spinneret and electrospinning technology to prepare polyvinyl pyrrolidone / iron tetroxide magnetic composite nanofibers [Journal of Chemistry in Universities, 2006, 27(10), 2002-2004]; Qingbiao Yang, et al. used a single spinneret and electrospinning technology to prepare Fe2O3nanoparticles / Eu(DBM)3(Bath) / PVP composite dual-functional magneto-optical nanofibers [Journal of Colloid and Interface Science, 2010, 350, 396-401]; Dong Xiangting et al. prepared Fe3O4 / Eu(BA)3phen / PVP magneto-optical dual-functional composite nanofibers by electrospinning technology [Journal of Nanoparticle Research, 2012, 14(10): 1203-1209]; Dong Xiangting et al. prepared Eu(BA)3phen / PANI / PVP optoelectronic dual-functional composite nanofibers by using a single spinneret and electrospinning technology [Journal of Chemistry in Universities, 2012, 33(8), 1657-1662]. Electrospinning technology has the advantages of simple equipment, easy control of the preparation process, adjustable product morphology, and easy industrial production, making it one of the important methods for preparing functional micro-nano fiber materials. At present, some people have used TPU as an electrospinning template and matrix to prepare TPU / TiO2 / PANI fibers [Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2023, 664:131111] and SrAl2O4:Eu 2+@TPU fluorescent anti-counterfeiting fiber membrane [Chemical Engineering Journal, 2021,405: 126949]. Pinar et al. used PCL as an electrospinning template and matrix, and successfully prepared PCL and PCL / GO nanofibers by electrospinning technology [European Polymer Journal, 2022, 165: 111000]. Using a mixture of PCL and TPU as an electrospinning template and a matrix of the fiber membrane, an electrospinning technology was used to prepare a superelastic and stretchable Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane with excellent red fluorescence and shape memory properties, which is used in anti-counterfeiting and information encryption storage, realizing dual-mode anti-counterfeiting and information encryption storage of fluorescence and shape memory, which has not been reported so far.
[0008] When using electrospinning technology to prepare nanomaterials, the type of raw materials, the molecular weight of the polymer template, the composition of the spinning solution, the spinning process parameters and the structure of the spinneret all have an important influence on the morphology and size of the final product. The present invention adopts electrospinning technology and uses a 12# stainless steel syringe needle as a spinneret to add a certain amount of two polymers, polycaprolactone PCL with thermo-induced shape memory and heat-shrinkable polyurethane TPU with superelastic stretchability, into the spinning solution. N,N -A mixed solvent of dimethylformamide (DMF) and dichloromethane (CH2Cl2) was prepared by adding Eu(TTA)3(TPPO)2 into an electrospinning solution; the electrospinning technology was applied to electrospinning, and a rotating drum was used as a receiving device. Under the optimal process conditions, Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane was prepared, which had excellent red fluorescence and shape memory properties and was used in anti-counterfeiting and information encryption storage, realizing dual-mode anti-counterfeiting and information encryption storage of fluorescence and shape memory, thereby improving the anti-counterfeiting and information encryption levels, and had important application prospects. Summary of the invention
[0009] In the background technology, a single spinneret is used, and electrospinning technology is used to prepare polyvinyl pyrrolidone / ferrous oxide composite magnetic nanofibers, PAN / Eu(BA)3phen composite luminescent nanofibers, conductive polyaniline PANI nanofibers, Eu(BA)3phen / PANI / PVP optoelectronic dual-function composite nanofibers, Fe3O4 / Eu(BA)3phen / PVP and Fe2O3nanoparticles / Eu(DBM)3(Bath) / PVP composite dual-function magneto-optical nanofibers, TPU-based fibers and PCL-based nanofibers; the raw materials, templates, solvents and final target products used are different from those of the method of the present invention. The present invention adopts electrospinning technology and uses ordinary syringe needles to prepare Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membranes, which have excellent red fluorescence and shape memory properties, are applied to anti-counterfeiting and information encryption storage, realize fluorescence and shape memory dual-mode anti-counterfeiting and information encryption storage, improve anti-counterfeiting and information encryption capabilities, and provide a new material for the field of anti-counterfeiting and information encryption.
[0010] The present invention is implemented as follows: firstly, a europium complex Eu(TTA)3(TPPO)2 is prepared by a precipitation method; a certain amount of polycaprolactone PCL and heat shrinkable polyurethane TPU are added to N,N -Dimethylformamide DMF and dichloromethane CH2Cl2 mixed solvent, and then add Eu(TTA)3(TPPO)2 to prepare electrospinning solution; electrospinning is performed using electrospinning technology, using a 12# stainless steel syringe needle as a spinneret, and a rotating drum as a receiving device. Under the optimal process conditions, Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is prepared. The steps are as follows: (1) Preparation of Eu(TTA)3(TPPO)2 complex by precipitation method 1.7596 g Eu2O3 was dissolved in 10 mL concentrated HNO3, heated at 120 °C for nitration to obtain Eu(NO3)3, and after cooling, 20 mL of anhydrous ethanol was added to obtain an ethanol solution of europium nitrate. 6.6670 g 2-thenoyltrifluoroacetone HTTA and 5.5680 g triphenylphosphine oxide TPPO were dissolved in 200 mL of anhydrous ethanol, and then the ethanol solution of europium nitrate was added to the mixed solution of HTTA and TPPO to produce precipitation. The pH value of the mixed solution was adjusted to 6.5, heated at 60 °C with magnetic stirring for 3 h, and then continued to stir at room temperature for 12 h. The product was centrifuged and washed with deionized water and ethanol three times in sequence, and finally dried in a drying oven at 60 °C for 12 h to obtain Eu(TTA)3(TPPO)2 complex. (2) Preparation of electrospinning solution Weigh 0.6 g of PCL with a molecular weight of 80,000 and 1.4 g of TPU with a molecular weight of 88,000, dissolve them in a mixed solvent of 6 mL of DMF and 12 mL of dichloromethane, stir at 30 °C for 3 h, then add 3 g of Eu(TTA)3(TPPO)2, and continue stirring to obtain Eu(TTA)3(TPPO)2 / PCL / TPU electrospinning solution; (3) Preparation of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane by electrospinning technology 4 mL of electrospinning solution was added into a 10 mL plastic syringe with a 12# stainless steel needle. The rotating drum was used as a receiving device and the rotation speed was 800 r·min. -1 The spinning voltage was 12 kV, the spinning distance was 15 cm, the ambient temperature was 20 °C-30 °C, and the relative humidity was 20%-50%. Electrospinning was carried out. After the electrospinning solution was completely exhausted, the fiber membrane was removed from the drum to obtain the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane.
[0011] The Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane prepared in the above process is composed of smooth micron fibers, which are randomly arranged, with a fiber diameter of 1.03±0.05 μm and a fiber membrane thickness of 140 μm. Under the excitation of 365nm ultraviolet light, the sample emits bright red fluorescence. The Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has superelastic stretchability and a breaking strength of 9.229 MPa, and the elongation at break is 133.727%; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good water resistance, and the water contact angle is 111.0º; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good shape memory properties, the shape fixation rate is 91.88%±0.87%, and the shape recovery rate is 73.17%±1.36%; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good red fluorescence shape memory properties, which can be used in anti-counterfeiting and information encryption storage, realizing fluorescence and shape memory dual-mode anti-counterfeiting and information encryption storage, and achieving the purpose of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is the XRD spectrum of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 2 is a SEM photo of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane, which also serves as an abstract figure; Figure 3 is the diameter distribution histogram of the fibers in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 4 This is the excitation spectrum of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 5 It is the emission spectrum of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 6 is the CIE chromaticity coordinate diagram of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 7 is the stress-strain curve of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Figure 8 This is the water contact angle test diagram of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Fig. 9 This is the SEM photo of the unstretched fiber membrane after heating of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Fig.10 is the diameter distribution histogram of the fibers in the unstretched fiber membrane after heating of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Fig.11 This is the SEM photo of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after heating and stretching to fix the shape; Fig.12 is the diameter distribution histogram of the fibers in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after heating, stretching and fixing the shape; Fig.13 This is the SEM photo of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after heating and shape recovery; Fig.14 is the diameter distribution histogram of the fibers in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after the heating shape recovery; Fig.15 This is the excitation spectrum of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after its shape is restored after heating; Fig.16 This is the emission spectrum of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after its shape is restored after heating; Fig.17This is the CIE chromaticity coordinate diagram of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after the fiber membrane is heated and its shape is restored; Fig.18 This is a diagram showing the shape memory effect of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane; Fig.19 This is a diagram of the application of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane in fluorescent anti-counterfeiting and information encryption storage process. DETAILED DESCRIPTION
[0013] The purity of europium oxide used in the present invention is 99.99%, 2-thenoyltrifluoroacetone HTTA, triphenylphosphine oxide TPPO, nitric acid, anhydrous ethanol, ammonia water, polycaprolactone PCL with a molecular weight of 80,000, and heat-shrinkable polyurethane TPU with a molecular weight of 88,000. N, N -Dimethylformamide (DMF) and dichloromethane were both commercially available analytically pure products; deionized water was homemade in the laboratory; the glass instruments and equipment used were commonly used in the laboratory.
[0014] Example: 1.7596 g Eu2O3 was dissolved in 10 mL concentrated HNO3, heated at 120 °C for nitration to obtain Eu(NO3)3, and after cooling, 20 mL of anhydrous ethanol was added to obtain an ethanol solution of europium nitrate. 6.6670 g 2-thenoyltrifluoroacetone HTTA and 5.5680 g triphenylphosphine oxide TPPO were dissolved in 200 mL of anhydrous ethanol, and then the ethanol solution of europium nitrate was added to a mixed solution of HTTA and TPPO to produce a precipitate. The pH value of the mixed solution was adjusted to 6.5, heated at 60 °C and magnetically stirred for 3 h, and then stirred at room temperature for 12 h. The product was centrifuged and washed with deionized water and ethanol three times in sequence, and finally dried in a drying oven at 60 °C for 12 h to obtain a Eu(TTA)3(TPPO)2 complex; 0.6 g PCL with a molecular weight of 80,000 and 1.4 g TPU with a molecular weight of 88,000 were weighed. g, dissolved in a mixed solvent of 6 mL DMF and 12 mL dichloromethane, stirred at 30 °C for 3 h, then 3 g Eu(TTA)3(TPPO)2 was added, and stirring was continued to obtain Eu(TTA)3(TPPO)2 / PCL / TPU electrospinning solution; 4 mL of the electrospinning solution was added into a 10 mL plastic syringe with a 12# stainless steel needle, and the rotating drum was used as a receiving device, with a rotation speed of 800 r·min -1, spinning voltage is 12 kV, spinning distance is 15 cm, ambient temperature is 20 ° C-30 ° C, relative humidity is 20%-50%, electrospinning is carried out, and after the electrospinning solution is completely exhausted, the fiber membrane is removed from the drum to obtain Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane. The rare earth complex Eu(TTA)3(TPPO)2 in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has a weak broad diffraction peak between the diffraction angles of 15°-35°, which belongs to the amorphous diffraction peak. The two diffraction peaks at 21.7° and 23.9° correspond to the diffraction peaks of the (110) crystal plane and the (200) crystal plane of the semi-crystalline structure of PCL, respectively. The diffraction peak of TPU is between 18-24°, corresponding to the mixed phase of its hard phase ordered structure and amorphous phase disordered structure, see Figure 1 As shown; the thickness of the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is 140 μm, and it is composed of smooth micron fibers, which are arranged in a disordered manner. Figure 2 As shown; the diameter of the fiber in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is 1.03±0.05 μm, see Figure 3 As shown; with 616 nm as the monitoring wavelength, Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has two obvious broad excitation peaks at 275 nm and 365 nm, which are the excitation peaks generated by the π→π* electronic transition of the ligand in the Eu(TTA)3(TPPO)2 complex, see Figure 4 As shown in Figure 2, under the excitation of 356 nm ultraviolet light, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has obvious emission peaks at 580 nm, 593 nm and 616 nm, corresponding to the emission peaks of Eu ions. 5 D0→ 7 F0, 5 D0→ 7 F1 and 5 D0→ 7 F2 transition, see Figure 5 As shown; under 356 nm ultraviolet light excitation, Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane emits bright red fluorescence with chromaticity coordinates of (0.656, 0.330), see Figure 6 As shown; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has superelastic stretchability, a breaking strength of 9.229 MPa, and a breaking elongation of 133.727%, see Figure 7As shown; Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good water resistance, and the water contact angle is 111.0º, see Figure 8 As shown in FIG. 1 ; after the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane was heated at 70 ºC for 5 minutes and cooled to room temperature, the surface of the fiber membrane became rough and the fiber diameter distribution became uneven, as shown in FIG. Fig. 9 As shown in FIG. 2 ; after the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane was heated at 70 ºC for 5 minutes and cooled to room temperature, the fiber diameter was 1.76±0.04 μm, see Fig.10 As shown in FIG. 1 ; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is heated and stretched at 70°C for 5 minutes, and the fibers in the fiber membrane after the stretching shape is fixed at room temperature become a microarray, as shown in FIG. Fig.11 As shown in the figure, the diameter of the fiber in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after being heated and stretched at 70 ºC for 5 minutes and then stretched to room temperature and fixed in shape is 1.47±0.02 μm. Fig.12 As shown in FIG. 1 ; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is heated at 70 ºC for 5 minutes and then cooled to room temperature. After the shape of the fiber membrane is restored, the fibers have returned to a disordered state, as shown in FIG. Fig.13 As shown in FIG. 1 ; the diameter of the fiber in the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane after being heated at 70 ºC for 5 minutes and cooled to room temperature after the shape is restored is 1.69±0.06 μm, see Fig.14 As shown in the figure; with 616 nm as the monitoring wavelength, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is heated at 70 ºC for 5 minutes and then cooled to room temperature. After the shape of the fiber membrane is restored, there are two obvious broad excitation peaks at 275 nm and 365 nm, which are the excitation peaks generated by the π→π* electronic transition of the ligand in the Eu(TTA)3(TPPO)2 complex, see Fig.15 As shown in the figure; under the excitation of 356 nm ultraviolet light, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is heated at 70 ºC for 5 minutes and then cooled to room temperature. After the shape of the fiber membrane is restored, there are obvious emission peaks at 580 nm, 593 nm and 616 nm, corresponding to the emission peaks of Eu ions, respectively. 5 D0→ 7 F0, 5 D0→ 7 F1 and 5 D0→ 7 F2 transition, see Fig.16As shown; under the excitation of 356 nm ultraviolet light, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane is heated at 70 ºC for 5 minutes and then cooled to room temperature. After the shape is restored, the fiber membrane emits bright red fluorescence with chromaticity coordinates of (0.639, 0.320), see Fig.17 As shown; the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good shape memory properties, the shape fixation rate is 91.88%±0.87%, the shape recovery rate is 73.17%±1.36%, and after kneading and stretching tests, it shows good shape memory performance. Fig.18 In order to explore the practical application of Eu(TTA)3(TPPO)2 / PCL / TPU fiber membrane as an anti-counterfeiting and information encryption storage medium, an anti-counterfeiting and information storage encryption system was independently designed and constructed. Fig.19 As shown, invisible blue fluorescent ink is used as ink, and then a customized QR code stamp coated with the ink is used to stamp a QR code on the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane. It can be seen that the QR code stamp pattern coated with invisible blue fluorescent ink emits bright blue fluorescence under 365nm ultraviolet light excitation. Under natural light, the QR code pattern on the fiber membrane cannot be observed by the naked eye. However, under 365 nm ultraviolet light, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane will emit bright red fluorescence, and the QR code information stored on the fiber membrane will emit bright blue fluorescence, realizing fluorescent anti-counterfeiting, and the blue fluorescent QR code information can be recognized by a mobile phone. Next, the fiber membrane is heated and stretched at 70 °C for 5 min to deform it, and then cooled to a fixed shape. It can be seen that the fiber membrane and the QR code information are deformed due to stretching, and the mobile phone cannot recognize and read them. However, due to its unique shape memory effect, the fiber membrane can be heated at 70 °C for 5 min to deform it. min and the stored QR code information can also be restored to its original state, and the QR code can still be easily recognized by the mobile phone to read the information, realizing the dual-mode anti-counterfeiting of fluorescence and shape memory and information encryption storage.
[0015] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. Superelastic stretchable fluorescent shape memory dual-mode anti-counterfeiting information encryption electrospun fiber membrane, characterized in that: It is composed of micron-fibers with smooth surfaces. The fibers are arranged in a disordered manner. The diameter of the fibers is 1.03±0.05 μm. The fiber membrane has superelasticity, stretchability, red fluorescence and shape memory properties. The thickness of the fiber membrane is 144 μm.
2. A preparation technology of the superelastic stretchable fluorescent shape memory dual-mode anti-counterfeiting information encrypted electrospun fiber membrane as claimed in claim 1, characterized in that: by N,N -Dimethylformamide DMF and dichloromethane CH2Cl2 are used as a mixed solvent, a mixture of two polymers, namely, thermo-induced shape memory polymer polycaprolactone PCL and heat-shrinkable polyurethane TPU with superelastic stretchability, is used as a spinning template and a matrix of a fiber membrane, and a red fluorescent Eu(TTA)3(TPPO)2 complex is used as a fluorescent substance. The electrospinning technology is used to prepare a product, namely, Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane, and the steps are as follows: (1) Preparation of Eu(TTA)3(TPPO)2 complex by precipitation method 1.7596 g Eu2O3 was dissolved in 10 mL concentrated HNO3, heated at 120 °C for nitration to obtain Eu(NO3)3, and after cooling, 20 mL of anhydrous ethanol was added to obtain an ethanol solution of europium nitrate. 6.6670 g 2-thenoyltrifluoroacetone HTTA and 5.5680 g triphenylphosphine oxide TPPO were dissolved in 200 mL of anhydrous ethanol, and then the ethanol solution of europium nitrate was added to the mixed solution of HTTA and TPPO to produce precipitation. The pH value of the mixed solution was adjusted to 6.5, heated at 60 °C with magnetic stirring for 3 h, and then continued to stir at room temperature for 12 h. The product was centrifuged and washed with deionized water and ethanol three times in sequence, and finally dried in a drying oven at 60 °C for 12 h to obtain Eu(TTA)3(TPPO)2 complex. (2) Preparation of electrospinning solution Weigh 0.6 g of PCL with a molecular weight of 80,000 and 1.4 g of TPU with a molecular weight of 88,000, dissolve them in a mixed solvent of 6 mL of DMF and 12 mL of dichloromethane, stir at 30 °C for 3 h, then add 3 g of Eu(TTA)3(TPPO)2, and continue stirring to obtain Eu(TTA)3(TPPO)2 / PCL / TPU electrospinning solution; (3) Preparation of Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane by electrospinning technology 4 mL of electrospinning solution was added into a 10 mL plastic syringe with a 12# stainless steel needle. The rotating drum was used as a receiving device and the rotation speed was 800 r·min. -1 The spinning voltage was 12 kV, the spinning distance was 15 cm, the ambient temperature was 20 °C-30 °C, and the relative humidity was 20%-50%. Electrospinning was carried out. After the electrospinning solution was completely exhausted, the fiber membrane was removed from the drum to obtain Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane, which was composed of smooth micron fibers. The fibers were arranged in a disordered manner. The diameter of the fiber was 1.03±0.05 μm, and the thickness of the fiber membrane was 140 μm. Under the excitation of 365 nm ultraviolet light, the sample emitted bright red fluorescence. The Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane had superelastic stretchability and a breaking strength of 9.229 MPa, the elongation at break is 133.727%, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good water resistance, the water contact angle is 111.0º, the Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good shape memory properties, the shape fixation rate is 91.88%±0.87%, and the shape recovery rate is 73.17%±1.36%. The Eu(TTA)3(TPPO)2 / PCL / TPU electrospun fiber membrane has good red fluorescence and shape memory properties, which can be used in anti-counterfeiting and information encryption storage, realizing fluorescence shape memory dual-mode anti-counterfeiting and information encryption storage.
Citation Information
Patent Citations
Assembly of polycaprolactone polyol-based polyurethane micro / nanofiber shape memory polymer by electrostatic spinning method
CN104562272A
Magnetic multicolor luminescent dual-functional two-layered composite nano-fiber membrane and preparation method thereof
CN106427114A
Self-repair material and article with shape memory effect and preparation method thereof
CN106633721A
Thermoplastic elastic shape memory material shapable at body temperature / room temperature
CN108192321A
Preparation method of flexible white fluorescence nanometer fiber membrane
CN108265400A